RATE OF COSTS ON INVESTMENT CAPITAL IN EMERGING MARKETS - Tereshenko, Oleg; Voloshanyk, Nataliya; Savchuk, Dmytro (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
To date, there is no adequate methodology for calculating the discount rate that would satisfy most financial analysts. The most common approach to determining the discount rate is to use the weighted average cost of capital (WACC) algorithm. The calculation of capital costs (discount rates) in emerging market countries (EM) is characterized by a number of problems related to the information inefficiency of the capital market, instability of demand for products, inflation, macroeconomic and legal uncertainty and a lack of proper payment discipline. Even more complex are the corresponding calculations during the financial crisis, accompanied by hyperinflation, a fall or significant fluctuations in the rate of the national monetary unit, trade wars, and the collapse of the banking system.Especially problematic for emerging markets is the calculation of the cost of equity (investment) capital. In developed markets, the classical CAPM model is used for these purposes. Taking into account the lack of an effective capital market in EM-related countries, it is quite difficult to determine the standard parameters of the model (risk-free rate of return, market risk premium, beta factor). Significant problems also lie in the sources and shadow schemes for paying high premiums for the risks of investing capital in EM. The aim of the paper is to substantiate recommendations on the procedure for calculating the rate of costs for own (investment) capital, taking into account the specifics of corporate activities in countries related to EM.